Efficient NFC coil antennas for fully enclosed metallic‐framed wearable devices. Issue 3 (18th December 2019) - Choi, Jaehyun; Lim, Sangho; Hong, Wonbin
Abstract : This study reports methods of alleviating the effect on inductive near‐field communication (NFC) coils caused by fully enclosed metallic‐frames for wearable devices such as smartwatches. Two techniques that, respectively, involve creating two short‐circuit passages to modify the distribution of the out‐of‐phase current on the metallic‐frame and reducing the out‐of‐phase current amplitude by devising an asymmetric coil topology is presented and studied in detail. Extensive simulation, prototyping and measurement are carried out for 13.56 MHz NFC applications. The presented techniques can, respectively, improve the induced magnetic coupling by 43 and 30% under identical conditions in the presence of the metallic frame. Furthermore, both methods comply with the NFC forum certification and do not require the need to increase the drive current and power consumption of the NFC circuitry.